New Studies on Humphry Davy: Introduction. (3rd July 2019) - James, Frank A. J. L.; Ruston, Sharon
Abstract : This special issue of Ambix brings together eight new studies on Humphry Davy together with an appreciation of the life and work of David Knight, much of whose scholarship was devoted to understanding Davy. Taken together they provide a much richer and more nuanced account of aspects of Davy's life, showing how he and his work fitted into the very complex and difficult social, cultural and political contexts of the opening decades of the nineteenth century. Taking as our starting point Thomas Carlyle's 1829 critique of modern science, in this introduction we weld together the themes that emerge from these papers, many of which ground their results in the project to publish Davy's Letters . This project has provided evidence that helps us critique the disciplinary boundaries that led to Davy becoming seen mostly as a chemist, while his friend Samuel Taylor Coleridge has generally been categorised as a poet. Such boundaries are now breaking down fruitfully as these essays all illustrate in their different ways. A consequence of the new understandings being produced, is that we need to consider anew what constitutes chemistry and chemists, how reputations and commemorations are constructed, the role of audiences (especially women) in developing knowledge and the use of language and literature, which, among other things, are key elements linking chemistry with other parts of society and culture. Davy provides an excellent location by which to address the historical issues involved, giving us an opportunity to balance carefully these and other components (such as human agency) in understanding how knowledge is constructed.